2006
DOI: 10.1021/jp061778v
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Structure of N,N-Bis(2-hydroxybenzyl)alkylamine:  Flexible Molecular Assembly Framework for Host without Guest and Host with Guest

Abstract: N,N-Bis(2-hydroxybenzyl)alkylamine derivatives form a cage-like assembly consisting of two molecules via inter- and intramolecular hydrogen bonds. The derivatives exhibit themselves as host to accept copper-ion guests under the double-oxygen-bridged dimeric system. Quantum chemical calculation suggested that the host-guest interaction is based on a charge-transfer coordination. Comparison of the crystal structures before and after complexation clarifies a rare example of a host-guest compound where the hosts m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Considering the factors involved in the ring opening reaction, our results show that, in the initial step, the hydrogen bonding between phenol derivatives and benzoxazine is primary when compare with phenol dissociation. Combining this with the previous X-ray structure analyses [11,13,14], we conclude that the obstructive effect of dimer in polymerization might result from the strong intramolecular hydrogen bond between the hydroxyl group of the phenol ring and the aza methylene group in the dimer.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Considering the factors involved in the ring opening reaction, our results show that, in the initial step, the hydrogen bonding between phenol derivatives and benzoxazine is primary when compare with phenol dissociation. Combining this with the previous X-ray structure analyses [11,13,14], we conclude that the obstructive effect of dimer in polymerization might result from the strong intramolecular hydrogen bond between the hydroxyl group of the phenol ring and the aza methylene group in the dimer.…”
Section: Discussionsupporting
confidence: 76%
“…The stabilization of a symmetrical compound through an intramolecular hydrogen bond inevitably gives us an asymmetric compound [11]. The X-ray structural analyses of dimers (4a-4c, 5a-5c, and 6a-6c) shows clearly that p-substituted based benzoxazines have inter-and intramolecular hydrogen bonds that stabilize the compounds [11,13,14]. Thus, after the single step of ring opening polymerization that produces the dimer, the stability of the network of inter-and intramolecular hydrogen bonding brings about the self termination.…”
Section: Mmentioning
confidence: 99%
“…Ligands of type 2 ( L C ) complex readily to a wide variety of transition metals including: Zr, V, Mo, Mn, Fe, and Cu However, for titanium only the preparation of 3a is known together with three Ti(substituted‐ L C ) 2 complexes using ligands related to 2 with R 1 , R 2 = Me (or its 3‐isomer), t Bu and R 3 = Et, n Pr, CH 2 CH 2 NMe 2 . Other than that, the nearest related titanium complexes we could identify (ca.…”
Section: Resultsmentioning
confidence: 99%
“…It is also similar to previous research, [11] indicating that zirconium ions of zirconia could form coordinate bonds with the unshared electrons on nitrogen atoms of ammonia and pyridine. Moreover, an earlier study [12] also demonstrated that nitrogen atoms of benzoxazine dimer could form coordination bonds with copper(II) of copper(II) acetate, which made the charges on the nitrogen atoms reduce from −0.34 to −0.55 eV due to the electrons flowing from nitrogen to copper atoms. Furthermore, the differences of N 1s binding energy between PC-a/La 2 O 3 composite and its residue, after elimination of the La 2 O 3 , will also verify the coordination interaction between transition metal and nitrogen atoms.…”
Section: Xps Analysismentioning
confidence: 96%